Negotiating Legitimacy: Binational Couples in the Face of Immigration Bureaucracy in Belgium and Italy - Odasso, Laura (Anthropologica, 2021)
Drawing from ethnographic research conducted with binational heterosexual couples negotiating their legitimacy in the face of immigration bureaucracy in Belgium and Italy, I explore the interplay between marriage migration governmentality and personal subjectivities. In a context of increased political scrutiny, I illustrate how binational couples wield their intimacy to become and stay legal; and how their experiences of the bureaucratic encounters impact on both partners’ agency, producing swinging emotions and improving their legal culture. In Belgium and Italy, marriage to a citizen remains a pathway towards securing residence for the migrant partner. Hence, in both countries these formalities, that I frame as a network of bordering practices, are increasingly – but differently – policed defining divergent marriage migration regimes but similar shared migratory careers for the couples. The potency of the legal-bureaucratic culture fashions the couples’ journey through immigration law and its street-level implementation. Nevertheless, beyond the opportunity structures and nationally anchored constraints, the analysis demonstrates that the partners’ agency similarly emerges from the migration management at large, their personal legal status and biographical resources, and interactions with intermediaries at the margin of immigration bureaucracy. Such agency – triggered by intimate intentions and expectations – is contingent and relational.